Estudo cinético da fermentação alcoólica com células imobilizadas em alginato de cálcio - Cordeiro, Patrícia Tavares (2008)
The study of alcoholic fermentation processes has gained prominence in recent years and at each day has increased the need to optimize the fermentation process, producing more and better to ensure an increase in alcohol production. Traditional processes of alcoholic fermentation using free yeast cells in the fermentation medium in a batch, fed-batch or continuous operation have drawbacks, such as the need to inoculate a large number of cells and to include a process for cells separation after the fermentation. On the other hand, processes using immobilized cells allow the operation without the need of a cell separation step after the fermentation, make possible to obtain high cell concentration per unit volume of the reactor, facilitate the biocatalysts reuse, and minimize the dead time besides giving a larger stability of cells. This study aimed to investigate the kinetics of the alcohol production using cells of Saccharomyces cerevisiae immobilized in sodium alginate. Tests were conducted to verify the stability of pellets obtained by using sodium alginate at concentrations of 3% and 2%. Pellets at the highest used concentration were found more stable to collapse. The treatment of the pellets with Al(NO3)3 increased further their stability against collapse. It was proposed a new bioreactor configuration that consisted of a batch stirred reactor with a perforated plate located in the center of the reactor, whose purpose was to prevent pellets fluctuation during the fermentation process. Several kinetic models were tested aiming at describing the substrate, product, and free cell concentration profiles in the bioreactor bulk and immobilized cells concentration profile into the pellets. The kinetic models of Monod, Hinshelwood, and Levenspiel were the most appropriate to describe the process of producing ethanol using cells of Saccharomyces cerevisiae immobilized in sodium alginate, and the kinetics parameters determined for the three models were suitable to represent the results for all conducted experiments.